FEATURES OF RAIL TRANSPORT AND THEIR ACCOUNTING IN THE REFORM OF THE INDUSTRY - A. Zhdanov (Вестник университета, 2018)
The transport potential of Russian railways plays an important role in ensuring sustainable social and economic development of the country. Railway transport has a number of significant features that should be considered with much attention into account both in the overall strategy of economic reforms in the country and in assessing the efficiency of the enterprises of the industry and the company JSC RZhD in general with obtaining objective quantitative characteristics. A more complete account of the features of rail transport is possible on the basis of improving the existing monitoring system of its activities. The monitoring system should be based on a systematic approach, the implementation of which will create prerequisites for the correct choice of an economically efficient system of information and analytical support for management decision-making